2006
DOI: 10.1074/jbc.m604802200
|View full text |Cite
|
Sign up to set email alerts
|

Rapid ATP-dependent Deadenylation of nanos mRNA in a Cell-free System from Drosophila Embryos

Abstract: Shortening of the poly(A) tail (deadenylation) is the first and often rate-limiting step in the degradation pathway of most eukaryotic mRNAs and is also used as a means of translational repression, in particular in early embryonic development. The nanos mRNA is translationally repressed by the protein Smaug in Drosophila embryos. The RNA has a short poly(A) tail at steady state and decays gradually during the first 2-3 h of development. Smaug has recently also been implicated in mRNA deadenylation. To study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(96 citation statements)
references
References 85 publications
8
88
0
Order By: Relevance
“…These results confirmed the specificity of the antibodies and suggested that the two polypeptides were isoforms of NOT1. Analysis with antibodies directed against the other anticipated subunits of the CCR4-NOT complex Jeske et al 2006) revealed a depletion of CAF1, CCR4, NOT1, NOT2, and NOT3 in the supernatant of the immunoprecipitation. The same polypeptides were enriched in the peptide eluate (Fig.…”
Section: Subunits Of the Ccr4-not Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…These results confirmed the specificity of the antibodies and suggested that the two polypeptides were isoforms of NOT1. Analysis with antibodies directed against the other anticipated subunits of the CCR4-NOT complex Jeske et al 2006) revealed a depletion of CAF1, CCR4, NOT1, NOT2, and NOT3 in the supernatant of the immunoprecipitation. The same polypeptides were enriched in the peptide eluate (Fig.…”
Section: Subunits Of the Ccr4-not Complexmentioning
confidence: 99%
“…Brain Tumor interacts with the regulatory protein 4EHP (Cho et al 2006), which was also present in the NOT1 precipitate, although its representation with a single peptide was below the threshold set for protein identification. Bicaudal is involved in post-transcriptional regulation of the nanos RNA, which is a substrate for the CCR4-NOT complex (Markesich et al 2000;Jeske et al 2006;Zaessinger et al 2006). …”
Section: Proteomic Analysis Of the Ccr4-not Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…In Drosophila, Smaug inhibits translation by blocking the formation of a competent translation initiation complex (9,23), by promoting deadenylation of target mRNAs leading to their destabilization and degradation (24)(25)(26), and by micro-RNA-independent recruitment of Argonaute 1 (Ago1) to target mRNAs (27). RNA immunoprecipitation combined with microarray analysis demonstrated that Smaug binds directly to numerous embryonic fly RNAs, including those encoding glycolytic enzymes, and components of the proteasome regulatory particle, the TRiC/CCT chaperonin, and lipid droplets (28).…”
Section: Discussionmentioning
confidence: 99%
“…Cup is recruited to oskar and nanos mRNAs by the 39 UTR binding proteins Bruno and Smaug, respectively. As for hunchback, additional mechanisms contribute to translational repression of these transcripts, including Bruno-driven mRNA oligomerization and Smaug-dependent deadenylation (Chekulaeva et al 2006;Jeske et al 2006;Zaessinger et al 2006). The examples of hunchback and nanos mRNAs illustrate that deadenylation often cooperates with mechanisms of translational control FIGURE 1.…”
Section: Cap-dependent Mechanismsmentioning
confidence: 99%